The Translation of Subject Pronoun I from English into Balinese in the Novel The Little Prince and Raja Cenik (e-Journal of Linguistics, 2023)
Balinese language has various varieties for its subject pronoun I.Investigating whether the translator presents these varieties whentranslating the English subject pronoun I into Balinese using the novelThe Little Prince and its Balinese translation Raja Cenik is the focus ofthis study. As the finding, the translator utilizes three different lexiconsin translating the English subject pronoun I into Balinese. Thesevarieties include Icang, Titiang and Gelah. The utilization of thesethree lexicons depends on the social status of the speakers and theinterlocutors. Balinese language possesses a number of differentlinguistic registers. Each of the register addresses the social status ofthe speakers and the interlocutors. The finding of this study shows thatculture and language are intricately interwoven to each other in thetranslation process.
Keywords: Subject Pronoun; Translation; Culture; English; Balinese